Augmented reality—The way forward in patient education for intracranial aneurysms? A qualitative exploration of views, expectations and preferences of patients suffering from an unruptured intracranial aneurysm regarding augmented reality in patient education - Urlings, Julie; Abma, Inger; Aquarius, René; Aalbers, Marlien; Bartels, Ronald; Maal, Thomas; Henssen, Dylan; Boogaarts, Jeroen (Frontiers in Bioengineering and Biotechnology, 2023)
Objectives: The goal of this project is to explore the views, expectations and preferences of patients with an unruptured intracranial aneurysm regarding the use of AR in patient education.To gain an in-depth understanding of the patients' perspective, a face-to-face interview study was conducted using an interview protocol with a predefined topic list. All interviews were audio-recorded and transcribed verbatim afterwards. Transcripts were analyzed using thematic content analyses. Coding was performed using Atlas.ti software.Results: Seventeen interviews were conducted. The views, expectations and preferences of patients regarding patient education with AR could be subdivided into 15 categories, which could be grouped into 4 general themes: (1) experiences with current patient education, (2) expectations of AR in patient education, (3) opportunities and limitations of AR, and (4) out-of-hospital use of an AR application. Patients' expectations were predominantly positive regarding improving patients' understanding of their medical situation and doctor-patient communication.Discusssion: This study suggests that patients with unruptured intracranial aneurysms are open to receive patient education regarding their disease with AR. Patients expect that AR models can help patients with intra-cranial aneurysms better understand their disease, treatment options and risks. Additionally, patients expect AR could improve doctor-patient communication.